The Trajectory of Global Education Policy Community-Based Management in El Salvador and the Global Reform Agenda - Edwards Jr., D. Brent (International and Development Education, 2018)
This book provides new insights into the phenomena of global education policies and international policy transfer. While both of these issues have gained popularity in the field of international and comparative education, there remains much that we do not know. In particular, while numerous studies have been produced which examine how global education policies-such as vouchers, charter schools, conditional-cash transfers, standardized testing, child-centered pedagogy, etc.-are implemented globally, we lack research which illuminates the origins and evolution of such policies. The book addresses this critical gap in our knowledge by looking at multiple aspects of the trajectory of a particular policy which was born in El Salvador in the early 1990s and subsequently went global. Edwards explicitly analyzes the trajectory of global education policy with reference to the role of international organizations and within the larger international political and economic dynamics that affected the overall country context of El Salvador.